The Role of Internal Limiting Membrane Flap for Highly Myopic Macular Hole Retinal Detachment: Improving the Closure Rate but Leading to Excessive Gliosis - Chen, Yiqi; Wang, Jun; Ye, Xin; Yu, Jiafeng; Tao, Jiwei; Lin, Li; Wu, Sulan; Qu, Jia; Shen, Lijun (Frontiers in Medicine, 2021)
Purpose: To investigate the surgical outcomes of the inverted internal limiting membrane (ILM) flap technique for macular hole retinal detachment (MHRD) in high myopia. Methods: This was a retrospective interventional study on 45 highly myopic eyes with MHRD after ILM peeling (n=24, peeling group) or the inverted ILM flap technique (n=21, inverted group). The inverted group was consisted of autologous blood (AB) subgroup (n=10) and perfluorocarbon liquid (PFCL) subgroup (n=11). MH closure, best-corrected visual acuity (BCVA), foveal microstructures, and excessive gliosis were analyzed during a follow-up of over 12 months. Results: The inverted group achieved a higher MH closure rate (95.24%) than the peeling group (41.67%; p<0.001). No significant difference was found in postoperative BCVA between the two groups (p=0.98) or between the closed MH with or without excessive gliosis (p =0.60). Excessive gliosis was identified in 9 eyes in the inverted group, and there was no difference in the incidence of excessive gliosis between the AB subgroup (4 in 10 eyes, 40%) and the PFCL subgroup (5 in 11 eyes, 45.45%) (p>0.999). Conclusion: The inverted ILM flap technique was effective in MH closure but had no advantage in postoperative BCVA and microstructural restoration. Excessive gliosis was only detected in the inverted group but did not affect the postoperative BCVA. Additionally, the incidence of excessive gliosis was not affected by adjuvants.